The access to administrative justice for prisoners under French law - Petit, Jacques (2021)
This study focuses on the access of detainees to French administrative justice; in this regard, the jurisprudence of the European Court of Human Rights is evaluated, as it plays a decisive role, especially when enforcing the provisions of the European Convention on Human Rights on the rights and freedoms of prisoners, who must be detained in conditions compatible with respect for human dignity. The French jurisdictional dualism (judicial and administrative) influences the designation of the competent judge to hear appeals brought by detainees to challenge the legality of the measures taken against them or to obtain compensation for the damage suffered. The distribution of competences between administrative and judicial judges regularly creates obstacles for detainees’ access to effective remedies. In this regard, it is postulated that the unification and institution of a specialized jurisdiction for prison disputes would allow detainees better access to justice in France.